مشكلات الطلبة في تحرير الأمثلة من القواعد النحوية بمعهد علوم الدين لهؤسماوي - Ediyani, Muhammad (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
The title of this research is about "The Problem of Students in Making an Example of the Nahwu’s Grammar (Study of Analysis in Ulumuddin Foundation Lhokseumawe)". As for the circumstances of students in Ulumuddin Foundation in Nahwu's lesson, the students are able to memorize Nahwu’s grammar such as mubtada ', khabar, fi'il, fa'il and other Nahwu’s grammar, but most of them are not able to make an example of the Nahwu's grammar. The purpose of this study to determine the problems of students in making an example of the Nahwu’s grammar and know the solution of teachers in solving the problem. The research method used is analytical research that is analyzing the obtained from the field with direct observation, interviews, and questionnaires. The results show that the problems faced by students in making examples of Nahwu's grammar because of the lack of Arabic vocabulary memorized, unable to apply the vocabulary in sentence form according to Nahwu's grammar, and the lack of enthusiasm of students in asking the teacher, and the teacher did not provide additional lessons to students due to time constraints. While the solution offered by the teacher to the students is the teacher gives a lot of vocabulary, then applied the vocabulary into the sentence, give examples from the verses of al-Qur'an and al-Hadist, and provide training once a week and teachers teach Nahwu with various methods so that students do not get bored.